Enhancing Quality in Early Childhood Education: The Effectiveness of Standard Operating Procedures - Dinah Khariyyah; Isra Hayati (Al-Irfan : Journal of Arabic Literature and Islamic Studies, 2026)
This study aims to analyze the effectiveness of the implementation of Standard Operating Procedures (SOPs) at Taska Qalby An Nur Malaysia. Standard Operating Procedures (SOPs) serve as work guidelines that function to regulate operational activities in a systematic, consistent, and standardized manner, thereby improving the quality of services in early childhood education institutions. This study employs a descriptive qualitative approach, with data collected through observation, interviews, and documentation studies. The research was conducted at Taska Qalby An Nur Malaysia, located in Cheras, Kuala Lumpur, Malaysia. The research informants consisted of the institution's management and staff who are directly involved in the implementation of Standard Operating Procedures (SOPs) within the taska. Data were analyzed using the interactive analysis model developed by Miles and Huberman, which includes data reduction, data display, and conclusion drawing and verification. The findings indicate that the implementation of Standard Operating Procedures (SOPs) at Taska Qalby An Nur Malaysia has been applied as a guideline for managing operational activities, particularly in financial management procedures. To enhance the effectiveness of the implementation of Standard Operating Procedures (SOPs), several strategic measures are required, including improving the dissemination and understanding of SOPs, providing training to enhance human resource competencies, strengthening the monitoring and evaluation system on a regular basis, ensuring the consistent implementation of regulations, and improving coordination between the taska management and all staff within the Foundation.